Caracterização fisiológica, fitoquímica e de atividades biológicas de plantas medicinais com potencial econômico para produção de fitoterápicos - Dutra, Jean Carlos Vencioneck (2019)
Plants of the Cactaceae and Lamiaceae Family are used by the population as food and in traditional medicine to treat or prevent diseases. The objective of this work was to evaluate the chemical composition, antioxidant, cytotoxic, anti-cytotoxic and antiproliferative activities of plant extracts of one plant of the Cactaceae Family and seven plants of the Lamiaceae Family, relating the results obtained to the phenological aspects or variations between species. The fruit and cladodes of Cereus jamacaru (Cactaceae) were collected at vegetative and fruiting stage and the total aerial part of Melissa officinalis, Mentha piperita, Ocimum basilicum, Ocimum selloi, Plecthanthus amboinicus, Plectranthus amboinicus "variegata" and Plectranthus ornatus (Lamiaceae) were collected for the production of hydroalcoholic extracts. Extracts were evaluated by preliminary phytochemical tests; the total content of flavonoids and rosmarinic acid were determined by spectrophotometric and HPLC techniques, respectively; the antioxidant activity was evaluated by the DPPH, ABTS, Fe2+ ion chelation activity and the ßcarotene/linoleic acid system; cytotoxicity and anti-cytotoxicity against cisplatin in human lymphocytes and antiproliferative effects on sarcoma cells 180 in vitro by the MTT assay; and antitumor activity and evaluation of mutagenicity in vivo. The fruit and cladodes of C. jamacaru were effective in promoting anticancer activity in vitro, and cladodes were able to inhibit cytotoxic damage induced by cisplatin in vitro and induced significant tumor reduction in sarcoma-induced rodents in vivo. Investigation on leaf variegation in Plecthanthus amboinicus showed that the variegation, in addition to morphological changes, leads to changes in the chemical composition and biological activity exhibited by this plant, leading to an increase in total flavonoid and rosmarinic acid content, as well as increased in vitro anticancer effects of Plectranthus amboinicus "variegata". The comparison between the other plants of the Lamiaceae Family studied suggests that rosmarinic acid biosynthesis occurs in detriment of flavonoid synthesis, and also suggests that Melissa officinalis and Mentha piperita, plant species with higher rosmarinic acid contente in this study, are more promising as natural antioxidants used to prevent cytotoxic damage and as anticancer agents. These results reinforce the use of these plants as much as food as in traditional medicine and provide information relevant to the development of new drugs.